Readings in Caribbean public sector economics - Andic, Fuat M. (Institute of Social and Economic Research KingstonJM)
Surveys the general fiscal problems of the Caribbean, taking stock of the literature. Deals with general fiscal problems. Aims to show the method of evaluating fiscal performance and fiscal requirements of a country which lopsidedly depends upon the exports of the output of one single industry. Outlines a set of normative and positive features regarding the role of the public sector in the region's transformation process. Studies six Caribbean countries as test cases and the applicability of the famous Wagner's Law is queried.